Extracellular nuclease from a thermophile, streptomyces thermonitrificans: production, purification and partial characterization of - double strand preferential - deoxyribonuclease activity - Patil, N. S.; Deshmukh, Satej S.; Shankar, V. (Process Biochemistry, 2005)
A thermophilic strain of Streptomyces themionitrificans produced high levels of extracellular nuclease (designated as nuclease Stn beta) when grown on nutrient broth glucose medium. Maximal nuclease activity (51 U ml(-1)) was obtained, in 40 h, when the culture was grown on modified NBG medium at 45 degreesC. The enzyme was purified to homogeneity with an overall recovery of 5.6% and a specific activity of 10,833. The relative molecular mass of the purified enzyme, determined by gel filtration, was 22.4 kDa and it showed an obligate requirement for Mn2+ for activity. The optimum pH and temperature of nuclease Stn beta were 8.0 and 45 degreesC, respectively. The enzyme was inhibited by Mg2+ CO2+, Cu2+, Zn2+ and Hg2+, inorganic phosphate, pyrophosphate, dithiothreitol, beta-mereaptoethanol, EDTA and NaCl. Nuclease Stn beta was stable to high concentrations of urea and organic solvents but susceptible to low concentrations of SDS and guanidine hydrochloride. Nuclease Stn beta is a multifunctional enzyme with substrate specificity in the order of dsDNA > ssDNA much greater than RNA. The end products of dsDNA hydrolysis were predominantly oligonucleotides (85-90%) and small amounts of 5' mononucleotides (10-15%) suggesting an endo mode of action. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Characterization; Endonuclease; extracellular nuclease; production; Purification; Streptomyces thermonitrificans

Purification, characterization and substrate specificity of thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) - Gote, M. M.; Khan, Mohammad Islam; Gokhale, D. V.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar (Process Biochemistry, 2006)
An extracellular thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) has been purified to homogeneity by chromatographic step, using Phenyl Sepharose CL-4B column. The specific activity of the enzyme was increased approximately 389-fold, from 1.03 U/mg protein to 400 U/mg protein. The molecular mass of the purified enzyme as determined by SDS-PAGE and gel filtration was 79.9 and 165.9 kDa, respectively, suggesting dimeric nature. The purified alpha-galactosidase is a non-glycosylated protein with a pI of 4.9. The pH and temperature optima for the purified enzyme are 6.5-7.0 and 65 degrees C, respectively. The alpha-galactosidase is stable over a broad pH range (3-9) and its half-life of inactivation (t(1/2)) at 70 degrees C is 30 min. The partial N-terminal sequence of alpha-galactosidase showed remarkable homology (80% similarity) with earlier reported alpha-galactosidase from B. stearothermophilus NUB 3621. The secondary structure of the enzyme determined by circular dichroism (CD) spectroscopy exhibited alpha/beta class of protein and showed temperature induced conformational forms below and above the transition temperature. The purified enzyme showed biphasic Arrhenius plot with break point at 55 degrees C for pNPG and 50 degrees C for melibiose, raffinose and stachyose. The enzyme hydrolyzes alpha-1-3, alpha-1-4, and alpha-1-6 galactosidic linkages and not the beta-galactosidic linkages. Synthetic substrates pNPG and oNPG had lower K-m and higher K-cat as compare to natural substrates, melibiose, raffinose, and stachyose. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha-galactosidase; Bacillus stearothermophilus (NCIM-5146); Purification; Secondary structure; thermostable enzyme

Purification and characterization of a lectin from endophytic fungus fusarium solani having complex sugar specificity - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (Archives of Biochemistry and Biophysics, 2007)
A lectin from the mycelial extract of an endophytic strain of Fusarium solani was purified. Its hemagglutinating activity was inhibited by glycoproteins possessing N-linked as well as O-linked glycans. The thermodynamics and kinetics of binding of glycans and glycoproteins to F. solani lectin Was Studied using SUH ace plasmon resonance. The lectin showed high affinity for asialofetuin, asia-lofibrinogen, asialofibrinogen, and thyroglobulin: and comparatively low affinity for mucin, fetuin, fibrinogen, and holotransferrin. Glycoproteins showed glycans with significant contribution from enthalpy and positive entropy, suggesting several fold higher affinity than their corresponding g the involvement of non-polar protein-protein interaction. Moreover, the higher affinity of the glycoproteins was due to their faster association rates and low activation energy. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: endophytic fungus; Fusarium solani; Lectin; Purification; SPR; Thermodynamic properties

Characterization of smallest active monomeric penicillin V acylase from new source: a yeast, rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Prabhune, Asmita; Suresh, C. G.; Pundle, Archana (Process Biochemistry, 2008)
An intracellular monomeric penicillin V acylase (PVA) of 36,000 Da exhibiting pI of 4.19, purified from newly identified yeast source, Rhodotorula aurantiaca (NCIM 3425). The enzyme was purified by hydrophobic interaction chromatography. The enzyme showed optimal activity at 45 degrees C and retained 80% activity after incubation at 45 degrees C and pH 5.5 for I h. The enzyme showed maximum activity at pH 5.5 and was very stable between pH 5.5-6.5 with optimum stability at pH 6.0. It exhibited 50% of its original activity after 30 min incubation at 60 degrees C. Enzyme hydrolyzed substrates with benzyl side chain but preferred penicillin V as primary substrate. N-terminally located serine supports the fact that it belongs to Ntn (N-terminal nucleophile)-hydrolase superfamily. The initial ten amino acid residues of R. aurantiaca PVA were identical to the initial sequence of NADH dehydrogenase (EC 1.6.99.3): however the enzyme lacks dehydrogenase activity. EGTA, EDTA, hexane and ethyl acetate stabilized the activity where as small chain alcohols inhibited it. 1,4-Dioxane, THF (tetrahydrofurane), phenol and benzyl alcohol severely inhibited enzyme activity while BME and DTT increased it. Tween 80 and Tween 20 highly enhanced the activity where as SIDS and Triton X-100 inhibited it. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Intracellular enzyme; N-terminal sequencing; Penicillin V acylase; Purification; Rhodotorula aurantiaca; Substrate specificity

Environment friendly crosslinked chitosan as a matrix for selective adsorption and purification of lipase of aspergillus niger - Trimukhe, K. D.; Mahadik, N. D.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2008)
Chitosan and its derivatives have been used as affinity matrices for purification of lipase from Aspergillus niger NCIM 1207. Trimellitic anhydride (TMA)-crosslinked deacetylated chitin adsorbed lipase selectively, yielding approximately 5-fold purification of the crude lipase with 70% yield. Further 9-fold purification occurred on eluting through Sephacryl-100. These results suggest that chitosan derivatives can be used as inexpensive biopolymer matrices for the purification of lipases for industrial applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Chitosan; Lipase; Matrix; Purification

Integrated process for extraction and purification of alcohol dehydrogenase from Baker's yeast involving precipitation and aqueous two phase extraction - Madhusudhan, M. C.; Raghavarao, K. S. M. S.; Nene, Sanjay (Biochemical Engineering Journal, 2008)
The potential of aqueous two phase extraction for the purification of alcohol dehydrogenase (ADH) from Baker's yeast (Saccharomyces cerevisiae) is demonstrated. An integrated process involving precipitation followed by aqueous two phase extraction (ATPE) is used for effective recovery of the enzyme. This is carried out in two schemes. In the first scheme, ammonium sulphate precipitation is carried out followed by ATPE of the precipitate after suspending it in buffer. While the second scheme involves polyethylene glycol precipitation followed by ATPE of the supernatant. The effect of various process parameters such as molecular weight of polymer, tie line length, phase volume ratio and neutral salt is investigated for enhancing the activity recovery of ADH. First scheme resulted in about 85% enzyme activity recovery of ADH with purification factor of 4.2 while the second scheme about 90% enzyme activity recovery with 6.6-fold purification. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Alcohol dehydrogenase; aqueous two phase extraction; enzyme extraction; Precipitation; Purification; Yeast

Production and single step purification of cyclodextrin glycosyltransferase from alkalophilic bacillus firmus by ion exchange chromatography - Savergave, Laman S.; Mule, Santosh S.; Jogdand, Vitthal V.; Nene, Sanjay N.; Gadre, Ramchandra V. (Biochemical Engineering Journal, 2008)
Production and purification of starch digesting cyclodextrin glycosyl transferase (CGTase) from alkalophilic Bacillus firmus was investigated. Fermentation was carried out in 141 bioreactor at 28 degrees C using a medium containing dextrin, yeast extract, peptone, (NH4)H2PO4 and MgSO4.7H(2)O. The extracellular enzyme was concentrated by tangential flow ultrafiltration. The concentrated enzyme was chromatographed using DEAE-sepharose and phenyl sepharose. DEAE-sepharose could be used to purify CGTase in a single step with 23.1 fold purification and 80.6% recovery. The enzyme obtained had homogeneity and the molecular weight was 76 kDa confirmed by SDS-PAGE. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkalophilic; Bacillus firmus; CGTase; cyclodextrin; Purification

Characterization of the smallest dimeric bile salt hydrolase from a thermophile brevibacillus sp. - Sridevi, N.; Srivastava, Sameer; Khan, Bashir Mohammad; Prabhune, Asmita Ashutosh (Extremophiles, 2009)
A thermophilic microorganism producing bile salt hydrolase was isolated from hot water springs, Pali, Maharashtra, India. This microorganism was identified as Brevibacillus sp. by 16S rDNA sequencing. Bile salt hydrolase (BSH) was purified to homogeneity from this thermophilic source using Q-sepharose chromatography and its enzymatic properties were characterized. The subunit molecular mass of the purified enzyme was estimated to be 28 kDa by SDS-PAGE and, 28.2 kDa by MALDI-TOF analysis. The native molecular mass was estimated to be 56 kDa by gel filtration chromatography, indicating the protein to be a homodimer. The pH and temperature optimum for the enzyme catalysis were 9.0 and 60A degrees C, respectively. Even though BSH from Brevibacillus sp. hydrolyzed all of the six major human bile salts, the enzyme preferred glycine conjugated substrates with apparent K (M) and k (cat) values of 3.08 mu M and 6.32 x 10(2) s(-1), respectively, for glycodeoxycholic acid. The NH2-terminal sequence of the purified enzyme was determined and it did not show any homology with other bacterial bile salt hydrolases. To our knowledge, this is the first report describing the purification of BSH to homogeneity from a thermophilic source.
Keywords: Bile salt hydrolase; Brevibacillus sp.; Dimeric intracellular enzyme; Purification; Thermophile

Purification and characterization of two distinct acidic phytases with broad pH stability from aspergillus niger NCIM 563 - Soni, S. K.; Magdum, A.; Khire, Jayant Malhar (World Journal of Microbiology & Biotechnology, 2010)
Aspergillus niger NCIM 563 produced two different extracellular phytases (Phy I and Phy II) under submerged fermentation conditions at 30A degrees C in medium containing dextrin-glucose-sodium nitrate-salts. Both the enzymes were purified to homogeneity using Rotavapor concentration, Phenyl-Sepharose column chromatography and Sephacryl S-200 gel filtration. The molecular mass of Phy I and II as determined by SDS-PAGE and gel filtration were 66, 264, 150 and 148 kDa respectively, indicating that Phy I consists of four identical subunits and Phy II is a monomer. The pI values of Phy I and II were 3.55 and 3.91, respectively. Phy I was highly acidic with optimum pH of 2.5 and was stable over a broad pH range (1.5-9.0) while Phy II showed a pH optimum of 5.0 with stability in the range of pH 3.5-9.0. Phy I exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. Similarly Phy II was strongly inhibited by Ag(+), Hg(2+) (1 mM) metal ions and Phy I was partially inhibited. Peptide analysis by Mass Spectrometry (MS) MALDI-TOF also indicated that both the proteins were totally different. The K (m) for Phy I and II for sodium phytate was 2.01 and 0.145 mM while V (max) was 5,018 and 1,671 mu mol min(-1) mg(-1), respectively. The N-terminal amino acid sequences of Phy I and Phy II were FSYGAAIPQQ and GVDERFPYTG, respectively. Phy II showed no homology with Phy I and any other known phytases from the literature suggesting its unique nature. This, according to us, is the first report of two distinct novel phytases from Aspergillus niger.
Keywords: Aspergillus niger; Phytase; Phytate; Poultry feed; Purification

Streptomyces nucleases - Joshi, Amruta Pramod; Deshmukh, Sumedha Sharad (Critical Reviews in Microbiology, 2011)
Streptomyces nucleases are widely distributed and multifunctional enzymes acting on both DNA and RNA. They occur extra as well as intracellularly and can be classified under sugar specific and sugar non-specific nucleases. Nucleases play different roles like analytical, biological, and nutritional. They are also used in programmed cell death. Although more than 20 nucleases are reported to date, very little information is available regarding their structure-function relationship, active site based sequence homology, and the probable mechanism of action. This review describes the history, occurrence, localization, production, purification, properties, and applications of Streptomyces nucleases.
Keywords: Applications; Endonuclease; extracellular; production; Purification; Substrate specificity

Biochemical characterization of a novel thermostable xyloglucanase from an alkalothermophilic thermomonospora sp. - Pol, Dipali; Menon, Vishnu; Rao, Mala (Extremophiles, 2012)
Xyloglucanase from an extracellular culture filtrate of alkalothermophilic Thermomonospora sp. was purified to homogeneity with a molecular weight of 144 kDa as determined by SDS-PAGE and exhibited specificity towards xyloglucan with apparent K (m) of 1.67 mg/ml. The enzyme was active at a broad range of pH (5-8) and temperatures (40-80A degrees C). The optimum pH and temperature were 7 and 70A degrees C, respectively. The enzyme retained 100% activity at 50A degrees C for 60 h with half-lives of 14 h, 6 h and 7 min at 60, 70 and 80A degrees C, respectively. The kinetics of thermal denaturation revealed that the inactivation at 80A degrees C is due to unfolding of the enzyme as evidenced by the distinct red shift in the wavelength maximum of the fluorescence profile. Xyloglucanase activity was positively modulated in the presence of Zn2+, K+, cysteine, beta-mercaptoethanol and polyols. Thermostability was enhanced in the presence of additives (polyols and glycine) at 80A degrees C. A hydrolysis of 55% for galactoxyloglucan (GXG) from tamarind kernel powder (TKP) was obtained in 12 h at 60A degrees C and 6 h at 70A degrees C using thermostable xyloglucanases, favouring a reduction in process time and enzyme dosage. The enzyme was stable in the presence of commercial detergents (Ariel), indicating its potential as an additive to laundry detergents.
Keywords: Alkalothermophilic Thermomonospora sp.; Biotechnological applications; Purification; Thermostable; Xyloglucanase

Characterization of smallest active monomeric lipase from novel rhizopus strain: application in transesterification - Kantak, Jayshree B.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2012)
An extracellular lipase-producing fungus was isolated from oil-rich soil. This fungus belongs to the genus Rhizopus and clades with Rhizopus oryzae. Lipase was purified to homogeneity from this novel fungal source using ammonium sulphate precipitation followed by Q-Sepharose chromatography. The extracellular lipase was purified 8.6-fold, and enzymatic properties were studied. The molecular mass of the purified enzyme was estimated to be 17 kD by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and 16.25 kD by matrix-assisted laser desorption ionization/time-of-flight analysis. The native molecular mass was estimated to be 17.5 kD by gel filtration, indicating the protein to be monomer. The optimum pH and temperature for the enzyme catalysis were 7.0 A degrees C and 40 A degrees C, respectively. Enzyme was stable in pH range 6.0-7.0 and retains 95-100% activity when incubated at 50 A degrees C for 1 h. The pI of the purified lipase was 4.2. Enzyme was stable in the organic solvents such as ethanol, hexane and methanol for 2 h. Purified enzyme was used for transesterification of oleic acid in the presence of ethanol for production of oleic acid ethyl ester with a conversion efficiency of 66% after 24 h at 30 A degrees C.
Keywords: Lipase; Low molecular weight; Purification; Rhizopus; transesterification

Downstream processing of extracellular phytase from aspergillus niger: chromatography process vs. aqueous two phase extraction for its simultaneous partitioning and purification - Bhavsar, Kavita P.; Kumar, V. Ravi; Khire, Jayant Malhar (Process Biochemistry, 2012)
The application of single step aqueous two-phase extraction (ATPE) for the downstream processing of phytase from Aspergillus niger NCIM 563, produced under solid state fermentation, has been studied and compared with the traditional multi-step procedure involving salt precipitation and column chromatography. High phytase recovery (98.5%) within a short time (3 h) and improved thermostability was attained by ATPE in comparison to 20% recovery in 96 h by chromatography process.The ATPE method, therefore, seems to be an interesting alternative for simultaneous partitioning and purification of phytase. The influence of system parameters; such as, phase forming salts, polymer molecular weight and system pH on the partitioning behavior of phytase was evaluated. The ATPE system consisting of combination of polyethylene glycol (PEG) 6000 and 8000(10.5%) and sodium citrate (20.5%) resulted in one-sided partitioning of phytase in bottom phase with a purification factor of 2.5. This is the first report on phytase purification using liquid-liquid extraction and the results are likely to be beneficial in the poultry feed industry. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aspergillus niger; liquid-liquid extraction; Phytase; Polyethylene glycol; Purification

Production, purification, and characterization of a beta-glucosidase of penicillium funiculosum NCL1 - Ramani, Gurusamy; Meera, Balasubramanian; Vanitha, Chinnathambi; Rao, Mala; Gunasekaran, Paramasamy (Applied Biochemistry and Biotechnology, 2012)
Penicillium funiculosum NCL1, a filamentous fungus, produced significantly higher levels of beta-glucosidase. The effect of initial pH, incubation temperature, and different carbon sources on extracellular beta-glucosidase production was studied in submerged fermentation. At 30 A degrees C with initial pH 5.0, enzyme production was increased by 48-fold upon induction with paper mill waste, as compared to commercial cellulose powder. In zymogram analysis, four isoforms of beta-glucosidases were observed with wheat bran whereas a minimum of one isoform was observed with other carbon sources. A major beta-glucosidase (Bgl3A) with the apparent molecular weight of similar to 120 kDa, induced by paper mill waste, was purified 19-fold to homogeneity, with a specific activity of 1,796 U/mg. Bgl3A was a monomeric glycoprotein with 29% of neutral carbohydrate content. It showed optimum activity at pH 4.0 and 5.0, optimum temperature at 60 A degrees C, and exhibited a half-life of 1 h at 60 A degrees C. K (m) of Bgl3A was found to be 0.057 mM with p-nitrophenyl beta-d-glucoside and V (max) was 1,920 U/mg. The purified enzyme exhibited glucose tolerance with a K (i) of 1.5 mM. Bgl3A readily hydrolyzed glucosides with beta-linkage. Bgl3A activity was enhanced (156%) by Zn2+ and was not affected by other metal cations and reagents. The supplementation of Bgl3A (5 U/mg) with Trichoderma reesei cellulase complex (5 FPU/mg) resulted in about 70% of enhanced glucose production, which emphasizes the industrial importance of Bgl3A.
Keywords: beta-Glucosidase; Paper mill waste; Penicillium funiculosum NCL1; Purification; Thermostability

Purification and biochemical characterization of endoglucanase from Penicillium pinophilum MS 20 - Pol, Dipali; Laxman, Ryali Seeta; Rao, Mala (Indian Journal of Biochemistry & Biophysics, 2012)
Cellulases find increasing prominence in sustainable production of fuel and feedstock from lignocellulosic biomass. The purification and biochemical characterization of individual components of cellulase complex is important to understand the mechanism of their action for the solubilization of crystalline cellulose. In this study, an extra-cellular endoglucanase isolated from culture filtrate of Penicillium pinophilum MS 20 was purified to homogeneity by ammonium sulphate precipitation, ion-exchange chromatography and gel filtration. The purified endoglucanase (specific activity 69 U/mg) was a monomeric protein with molecular mass of 42 kDa, as determined by SDS-PAGE. The endoglucanase was active over a broad range of pH (4-7) with maximum activity at pH 5 and showed optimum temperature of 50 degrees C. It retained 100% activity at 50 degrees C for 6 h and half- lives of 4 h and 3 h at 60 degrees C and 70 degrees C, respectively. The kinetic constants for the endoglucanase determined with carboxymethyl cellulose as substrate were V-max of 72.5 U/mg and apparent K-m of 4.8 mg/ml. The enzyme also showed moderate activity towards H3PO4 swollen cellulose and p-nitrophenyl beta-D-glucoside, but no activity towards filter paper, Avicel and oat spelt xylan. The activity was positively modulated by 47, 32 and 25% in the presence of Co2+, Zn2+ and Mg2+, respectively to the reaction mixture. The wide pH stability (4-7) and temperature stability up to 50 degrees C of endoglucanase makes the enzyme suitable for use in cellulose saccharification at moderate temperature and pH.
Keywords: Biochemical properties; Carboxymethyl cellulose; Endoglucanase; Penicillium pinophilum MS 20; Purification

Purification and characterization of an antioxidant protein (similar to 16 kDa) from Terminalia chebula fruit - Srivastava, Pratibha; Raut, Hema N.; Wagh, Renuka S.; Puntambekar, Hemalata M.; Kulkarni, Mahesh J. (Food Chemistry, 2012)
Terminalia chebula fruit is used as folk medicine in India and Southeast Asia. An antioxidant protein was isolated by bioassay guided fractionation of T. chebula fruit by homogenizing in the citrate phosphate buffer. The isolated protein (TCP-III) obtained from fruit was purified by gel chromatography and preparative HPLC, showed apparent molecular weight of 16 kDa by SDS-PAGE and MALDI-TOF/MS analyses. Amino acid sequence obtained by LC-MSE analysis showed homology with the predicted protein fragments of Populus trichocarpa, putative uncharacterized protein fragments from Oryza sativa and with fragments of 17 kDa thylakoid lumenal protein from Spinacia oleracea. TCP-III exhibited significant radical scavenging in DPPH, NO, H2O2 and ABTS assays. In addition, TCP-III inhibited oxidation of linoleic acid in beta-carotene bleaching assay, reduced ferric ions and chelated ferrous ions. The present finding demonstrates uniquely, for the first time, characterization of an antioxidant protein from T. chebula fruit. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 16 kDa protein molecule of T. chebula; Antioxidant and free radical scavenging activity; Characterization; Purification; Terminalia chebula fruit

Synthesis of Hofmann-based metal-organic frameworks incorporating a bis-pyrazole linker for various gas separations - Matthews, Brooke L.; Harvey-Reid, Nathan C.; Jangodaz, Elnaz; Scott, Victoria-Jayne; Polson, Matthew I. J.; Maibam, Ashakiran; BabaRao, Ravichandar; Telfer, Shane G.; Kruger, Paul E. (JOURNAL OF MATERIALS CHEMISTRY A, 2024)
Keywords: acetylene; C2H2/CH4; Ni; Purification; SPIN-CROSSOVER BEHAVIOR